HCV, a heuristic covering algorithm for extension matrix approach - Wu, Xingdong (University <Edinburgh> / Department of Artificial Intelligence: DAI research paper, 1992)
Abstract: "HCV is a heuristic attribute-based induction algorithm based on the extension matrix approach. By dividing the positive examples (PE) in a given example set into intersecting groups and adopting a set of strategies to find a heuristic conjunctive formula in each group which covers all the positive examples in the group and none of the negative examples (NE), it can find a covering formula in form [sic] of variable- value logic for PE against NE in low-order polynomial time. This paper presents the algorithm in detail and provides a comparison of it with ID3, a representative of the decision tree method based family of inductive algorithms."